2023
DOI: 10.1021/acscatal.3c02167
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Methane Combustion Activity by Modulating the Local Environment of Pd Single Atoms in Pd1/CeO2 Catalysts

Jinshu Tian,
Ru Kong,
Zhi Wang
et al.

Abstract: Reducing methane emissions is crucial for mitigating global warming. Developing highly efficient catalysts for low-temperature methane combustion is of great importance. Supported single-atom catalysts (SACs) have received significant attention in this regard. However, their long-term stability and activity remain challenging. In this study, we present a method for creating a highly active and thermally stable Pd 1 /CeO 2 catalyst by using thermal-shock synthesis (Pd 1 /CeO 2 -TS). By subjecting isolated Pd 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To further demonstrate the existence of Pd species in a single atom state on Pd/CN-60, CO adsorption at 303 K over Pd/CN and Pd/CN-60 catalysts is studied using the in situ DRIFTS technique, and the results are shown in Figure S8. For Pd/CN catalysts, there are three CO adsorption peaks at 2088, 1980, and 1928 cm –1 , which are assigned to linearly bound, bidentate bridged adsorption (Pd 2 –CO), and tridentate bridged adsorption (Pd 3 –CO) of CO molecules on the palladium species, respectively. , However, there are no Pd 2 –CO and Pd 3 –CO adsorption peaks in the range of 1900–2000 cm –1 ,and only a Pd 1 –CO adsorption peak is observed at 2090 cm –1 . The CO adsorption result further indicated that the Pd species on Pd/CN-60 mainly existed in a single atom state, which is consistent with the results of aberration-corrected HAADF–STEM.…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the existence of Pd species in a single atom state on Pd/CN-60, CO adsorption at 303 K over Pd/CN and Pd/CN-60 catalysts is studied using the in situ DRIFTS technique, and the results are shown in Figure S8. For Pd/CN catalysts, there are three CO adsorption peaks at 2088, 1980, and 1928 cm –1 , which are assigned to linearly bound, bidentate bridged adsorption (Pd 2 –CO), and tridentate bridged adsorption (Pd 3 –CO) of CO molecules on the palladium species, respectively. , However, there are no Pd 2 –CO and Pd 3 –CO adsorption peaks in the range of 1900–2000 cm –1 ,and only a Pd 1 –CO adsorption peak is observed at 2090 cm –1 . The CO adsorption result further indicated that the Pd species on Pd/CN-60 mainly existed in a single atom state, which is consistent with the results of aberration-corrected HAADF–STEM.…”
Section: Resultsmentioning
confidence: 99%
“…PtPdRhRuCe, CoMoFeNiCu, AuAgPtPdCu and PtPdCoNiFeCuAuSn) [ 26 , 38 ], single atoms (e.g. Ru, Pt, Pd and Co) [ 23 , 39 ] and metallic compounds (e.g. SiC, CoS, FeS 2 , Co 3 O 4 , MoS 2 , CoFeP x , LiMn 2 O 4 , LiCoO 2 , LiFePO 4 and Li-rich layered oxide/NiO heterostructures) [ 40–45 ].…”
Section: Hts Technique For Ultrafast Manufacturingmentioning
confidence: 99%